Tirnovo (since 1965 “VelikoTărnovo”) From Medieval Bulgarian Capital to Turkish Islamic Cultural Centre. A general overview - Machiel KIEL (Fayoum University, 2017)
Veliko Tărnovo, the former historical city of Tirnovo, today is the capital of a province (Okrăg) in N.E. Bulgaria. Tirnovo is located on the Yantra River and is famously known as the historical capital of the Second Bulgarian Empire. The subject matter research is exploring the history, art and architecture of Tirnovo through ages; and specifically during the Ottoman times (1393-1878), when became an Islamic cultural centre.  Tirnovo grew quickly, between the 12th and 14th centuries, to become the strongest Bulgarian fortification of the Middle Ages, and the most important political, economic, cultural and religious centre of the Second Bulgarian Empire. In the 14th century, as the Byzantine Empire weakened, Tirnovo claimed to be the “Third Rome”, based on its influential cultural aspect in Eastern Europe. This paper discusses the development of population, architecture and cultural of Tirnovo in Ottoman times. It was a flourished centre of Islamic culture, with considerable examples of almost all known types of ottoman buildings.